Effects of Second-Order Slip Flow and Variable Viscosity on Natural Convection Flow of CNTs−Fe3O4/Water Hybrid Nanofluids due to Stretching Surface. (19th March 2021) - Tulu, Ayele; Ibrahim, Wubshet
Abstract : This study deals with natural convection unsteady flow of CNTs − Fe 3 O 4 /water hybrid nanofluids due to stretching surface embedded in a porous medium. Both hybrid nanoparticles of SWCNTs − Fe 3 O 4 and MWCNTs − Fe 3 O 4 are used with water as base fluid. Effects of hybrid nanoparticles volume friction, second-order velocity slip condition, and temperature-dependent viscosity are investigated. The governing problem of flow is solved numerically employing spectral quasilinearization method (SQLM). The results are presented and discussed via embedded parameters using graphs and tables. The results disclose that the thermal conductivity of CNTs − Fe 3 O 4 / H 2 O hybrid nanofluids is higher than that of CNTs − H 2 O nanofluids with higher value of hybrid nanoparticle volume fraction. Also, the results show that momentum boundary layer reduces while the thermal boundary layer gros with higher values of temperature-dependent viscosity and second-order velocity slip parameters. The skin friction coefficient improves, and the local heat transfer rate decreases with higher values of nanoparticle volume fraction, temperature-dependent viscosity, and second-order velocity slip parameters. Furthermore, more skin friction coefficients and lower local heat transfer rate are reported in the CNTs − Fe 3 O 4 / H 2 O hybrid nanofluid than in the CNTs − H 2 O nanofluid. Thus, the obtained results are promising for the application of hybrid nanofluids in the nanotechnology and biomedicine sectors.